Dampak Pembelajaran Keselamatan Kerja Terhadap Pemahaman Prosedur Keselamatan Kapal Niaga pada Siswa Nautika di SMK Negeri 3 Ambon - Mashudi Rofik; Prapti Utami; Sarah Elisabeth Seilatu (Politeknik bumi Akpelni, 2026)
This study investigates the effect of safety-at-work learning on students’ understanding of merchant ship safety procedures among Nautical Department students at SMK Negeri 3 Ambon. A quantitative approach with a causal-associative design and ex post facto technique was employed. The population consisted of 100 students, and 80 respondents were selected using simple random sampling. Data were collected through a validated Likert-scale questionnaire and analyzed using descriptive statistics, Pearson correlation, and simple linear regression with IBM SPSS Statistics 25. The results show that safety-at-work learning is categorized as “good” (average 4.14), while students’ understanding of ship safety procedures is also “good” (average 4.04). A strong and significant positive correlation was found (r = 0.724, p < 0.001), and regression analysis (Ŷ = 1.205 + 0.685X, R² = 0.524) indicates that safety-at-work learning explains 52.4% of the variation in students’ understanding. It is concluded that structured and practice-based safety education significantly improves students’ comprehension of merchant ship safety procedures.